Three new species of the genus Mimetus Hentz, 1832 (Araneae: Mimetidae) from Yunnan-Guizhou Plateau of China - Gan, Jiahui; Mi, Xiaoqi; Irfan, Muhammad; Peng, Xianjin; Ran, Siyu; Zhan, Ying (European Journal of Taxonomy, 2019)
Three new species of the genus Mimetus Hentz, 1832 are described and named as M. bucerus sp. nov. (♂), M. lingbaoshanensis sp. nov. (♂♀) and M. yinae sp. nov. (♂♀). Detailed morphological descriptions, photos of the body and copulatory organs, line drawings of copulatory organs, as well as the distribution maps are provided.